Delineating bedrock outcrops and shallow superficial deposits in Southern Finland with LiDAR DEMs - Viitanen, Erkko (My University, 2024)
This study utilizes visual identification of topographical textures of bedrock outcrops and shallow superficial deposit areas (BOSS) that can be interpreted from remotely sensed Light Detection and Ranging (LiDAR) based Digital Elevation Models (DEM) from four different study areas in S Finland. Accuracy of new delineations for BOSS areas were tested on the field and with elevation profiles in ArcGIS Pro. These four study sites represent different Quaternary deposits and varying amounts of BOSS areas. Main research goals for this thesis were the measurement of accuracy and the amount of new BOSS areas digitized in 1: 4000, describe the textural characteristics associated with shallow superficial deposits and bedrock outcrops visible on DEM, determine the geological processes affected to the distribution and origin of shallow superficial deposits in recently glaciated landscapes. Results suggest that there is great potential for the refinement and update of BOSS areas via LiDAR DEM usage and applications. Bedrock outcrop areas were increased by 30% while shallow superficial deposit areas decreased by 1.3% from the original BOSS data produced by MML>K in a scale of 1: 10 000. New delineations were on average 3.5 m more accurate than the existing ones, interpreted from 2 terrain profiles from Muurla. Overall ruggedness of BOSS textures is apparent on DEM maps, and Terrain Ruggedness Index (TRI) supports this. Outcrops were visually easier to delineate on shaded relief maps compared to shallow superficial deposits. This is because of the protrusions, slopes, edges and fracture surfaces they exhibit. In Southern Finland glacial and glaciofluvial processes have impacted greatly on the origin and distribution of BOSS areas. Bedrock structures, rock type and bedding plane orientations also play important role. This study emphasises also the importance of field work and field inspections during a re-survey of BOSS areas.
Keywords: LiDAR, DEM, bedrock outcrops, shallow superficial deposits, Survey, Quaternary deposits